2011
DOI: 10.1007/s12070-011-0275-x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentations of Rhinosporidiosis: A Clinical Dilemma?

Abstract: Rhinosporidiosis is a chronic inflammatory disease common in India and Sri Lanka. Its manifestations are mostly nasal, though extranasal ones in head and neck region are not rare. Occasionally these presentations lead to diagnostic dilemma. Here we present some cases with its associated confusions if any. In this study thirty five patients were included. Extranasal manifestations were noted in nine cases. Two patients attended with laryngopharyngeal and one with lacrimal sac presentation-subsequent nasal endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…[ 7 ] Rhinosporidiosis is more prevalent among males in the age group of 10-40 years. [ 3 ] Similarly, male patients were more frequent in our series (10 cases out of 16; 62.5%) and majority were young aged (13 cases are in the age group of 11-30 years; 81.25%). Mode of infection is supposed to be trans-epithelial inoculation of organism in traumatized epithelium.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…[ 7 ] Rhinosporidiosis is more prevalent among males in the age group of 10-40 years. [ 3 ] Similarly, male patients were more frequent in our series (10 cases out of 16; 62.5%) and majority were young aged (13 cases are in the age group of 11-30 years; 81.25%). Mode of infection is supposed to be trans-epithelial inoculation of organism in traumatized epithelium.…”
Section: Discussionsupporting
confidence: 58%
“…Rhinosporidiosis was discovered by Malbran, as a sporozoon in 1892. [ 2 3 ] The same organism was first published by Seeber in 1900 and Ashworth describes its lifecycle in 1923. [ 6 ] Taxonomy of R. seeberi is still debatable and in last decade it was concluded that it is not a classic fungus, rather a human pathogen from Dermocystidium , the Rossette Agent, Ischthyophonus and Psorospermium clade - a clade of aquatic protistan parasites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 2 ] It is a cosmopolitan disease of human and domestic animals, prevalent in hot tropical climate of endemic zones like India, Sri Lanka, East Africa, parts of America and also encountered among expatriate population in the West. [ 3 4 ] Water and soil are the main reservoirs of infection and the endospores are transmitted through water and dust into the nasal mucosa by traumatic inoculation where they mature subepithelially and after maturation burst with release of sporangia into the tissues. [ 5 ] RS is characterized by a reddish, friable, polypoidal, hyperplastic mass mostly occurring in the nasal cavity and nasopharynx, however, sporadic occurrence in extra nasal sites is also observed.…”
Section: Introductionmentioning
confidence: 99%